Different Dosages of Corticosteroid and Routes of Administration in Mandibular Third Molar Surgery: a Systematic Review - Marie Kjærgaard Larsen; Thomas Kofod; Ann-Eva Christiansen; Thomas Starch-Jensen (Stilus Optimus, 2018)
Objectives: The objective of the present systematic review was to test the hypothesis of no difference in facial swelling, pain and trismus after surgical removal of mandibular third molar with different dosages of corticosteroids and administration routes. Material and Methods: A MEDLINE (PubMed), Embase database and Cochrane Library search in combination with a hand-search of relevant journals was conducted by including randomized controlled trials published in English until 1st December 2017. Results: Seven studies fulfilled the inclusion criteria. Considerable variation in the included studies prevented meta-analysis from being performed. Preoperative submucosal injection of corticosteroids significantly diminishes facial swelling, pain and trismus compared with placebo. However, different dosages of corticosteroid and administration routes reveal contrary results indicating that administration of a higher dosage of corticosteroids do not necessarily cause a further decrease in facial swelling, pain and trismus. Conclusions: Consequently, the optimal dosage of corticosteroids and administration route for diminishing postsurgical morbidity and improve quality of life after surgical removal of mandibular third molar is presently unknown. Therefore, further well-designed randomized clinical trials including a standardised protocol, patient-reported outcome measures and three-dimensional analysis of facial swelling is needed.